Academic Senate Minutes 2012-10-11 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes delayed. GE Experimental Course Process and Form – First Reading completed. President Report. Provost Report. Vice Chair Report. Posthumous MA degree request for Marcia K. Brown approved. Associated Students Report. Statewide Senator Report. Annual Report on International Programs. APC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Rep Report.